Pelatihan Penyusunan Rencana Pembangunan Jangka Menengah Kampung Di Distrik Oridek Kabupaten Biak Numfor - Marsi Adi Purwadi (UNIVERSITAS CENDERAWASIH, 2020)
The training of the village medium-term plan (RPJMK) in the Oridek district of Biak Numfor Regency was conducted to 1) improve the knowledge and understanding of Arapatur District/Village in the middle term plan village (RPJMK) in the Oridek district of Biak Numfor Regency, which complies with prevailing regulations, and 2) the creation and consistency between the planning, budgeting, implementation, and supervision of government programs from the district level to the village. This training was held at Anggaduber village of the Oridek district of Biak Numfor Regency. The results of the training showed that from the results of the Pree test, it was found that of the 20 participants who attended the training, 45.14 percent of participants did not understand the concepts and rules related to the planning of village development. The remainder, as many as 54.86 percent, has been aware of the concepts and rules relating to the planning of village development. As for the results of the post-test, it was found that from 48 participants who attended this training, 20.49 percent of participants did not understand the concepts and rules relating to the planning of village development. The remainder, as many as 79.51 percent, has been aware of the concepts and rules relating to the planning of village development. In the development planning in Anggaduber village, there has been a well-run, were in the preparation of the existing RPJMK village government has coordinated with the Ditrict and BPMK Biak Numfor Regency in looking at the direction and target of village development in supporting development in the Oridek District, Biak Numfor Regency, Papua Province, and state development.